2021
DOI: 10.3389/fcell.2020.601521
|View full text |Cite
|
Sign up to set email alerts
|

THBS1/CD47 Modulates the Interaction of γ-Catenin With E-Cadherin and Participates in Epithelial–Mesenchymal Transformation in Lipid Nephrotoxicity

Abstract: Hyperlipidemia, an important risk factor for cardiovascular and end-stage renal diseases, often aggravates renal injury and compromises kidney function. Here, histological analysis of human kidney samples revealed that high lipid levels induced the development of renal fibrosis. To elucidate the mechanism underlying lipid nephrotoxicity, we used two types of mouse models (Apoe−/− and C57BL/6 mice fed a 45 and 60% high-fat diet, respectively). Histological analysis of kidney tissues revealed high-lipid-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…30,49 The prominent pathological manifestations in the AS and AS + PD groups may be related to the changes of blood lipids and inflammation induced by lipid metabolism disorders in mice after the occurrence of atherosclerotic lesions. 21,34 Previous studies have shown that kidney damage related to lipid metabolic disorders usually begins with structural changes of renal tubules, manifested by vacuolar degeneration, brush border destruction and exfoliation of cells, 50,51 which is consistent with our experimental results. The results of histopathological staining suggested that when periodontitis exists alone in mice, its effect on inducing renal tissue damage is limited, whereas renal tissue damage was severe in AS mice in comparison; when periodontitis occurred in AS mice, the pre-existing renal tissue damage in AS mice was significantly exacerbated, demonstrating that periodontitis significantly induced renal tissue damage in AS mice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…30,49 The prominent pathological manifestations in the AS and AS + PD groups may be related to the changes of blood lipids and inflammation induced by lipid metabolism disorders in mice after the occurrence of atherosclerotic lesions. 21,34 Previous studies have shown that kidney damage related to lipid metabolic disorders usually begins with structural changes of renal tubules, manifested by vacuolar degeneration, brush border destruction and exfoliation of cells, 50,51 which is consistent with our experimental results. The results of histopathological staining suggested that when periodontitis exists alone in mice, its effect on inducing renal tissue damage is limited, whereas renal tissue damage was severe in AS mice in comparison; when periodontitis occurred in AS mice, the pre-existing renal tissue damage in AS mice was significantly exacerbated, demonstrating that periodontitis significantly induced renal tissue damage in AS mice.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in order to verify the above view and evaluate the effect of periodontitis on renal inflammation in AS mice, we detected three markers of renal inflammation, including TNF‐α, IL‐1β and Ly6G. As key proinflammatory cytokines, TNF‐α and IL‐1β are commonly used inflammatory markers, which play an important role in renal inflammation and kidney damage 17,21,46,47 . Especially, TNF‐α has been shown to play a central role in the structural and functional changes of the kidney associated with periodontitis and obesity 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, RESIS-TIN signaling may systemically increase susceptibility to diverse diseases. Moreover, the THBS network, whose ligand is highly expressed after LPS stimulation, increases the risk of inflammation [51,52], and the CD48 network, which is known to activate NK cells and contribute to diverse autoimmune diseases, is maintained even after periodontal therapy [53,54]. All this evidence indicates that typical periodontal treatment cannot be the sole strategy for complete immune recovery and necessitates consideration of other therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%